Islam dan Demokrasi: Pesrpektif Tafsir Maudhu’i - Muzayyin, Ahmad; Hidayat, Aleh; Muhyi, Asep Abdul (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
This research aims to explore contemporary issues regarding democracy in the context of the Al-Qur'an. This research uses a qualitative approach with descriptive methods and Maudhu'i interpretation. The formal object of this research is Al-Qur'an knowledge and contemporary issues, while the material object is verses in the Al-Qur'an related to democracy. Democracy in the Qur'an is considered something important and principled because democracy is a form of deliberation that produces agreement or consensus. The Qur'an has explained the principles that must exist in democracy, as contained in the letters ash-Syuara', an-Nahl, al-Hujurat, and an-Nisa'. These principles are in line with the principles of democracy in Indonesian state law, known by the acronym